Plausibility of a subglacial lake under Amundsenisen Icefield (Svalbard): spatially variable water content and sensitivity to thermal effect of snow and firn layers - Bucchignani, Edoardo; Mansutti, Daniela; Navarro Valero, Francisco José; Otero García, Jaime; Glowacki, Piotr (E.T.S.I. Telecomunicación (UPM), 2013)
Within our study of the plausibility of a subglacial lake under the Amundsenisen Icefield in Southern Spitzbergen, Svalbard achipelago (Glowacki et al., 2007), here we focus on the sensitivity of the system to the thermal effect of the firn and snow layers. Rough heat balance analysis shows that the firn layer plays an important role by driving the heat release to the atmosphere, so that its influence on the ice-water phase transition cannot be neglected (Bucchignani et al., 2012).